Anticancer clinical efficiency and stochastic mechanisms of belinostat - El Omari, Nasreddine; Bakrim, Saad; Khalid, Asaad; Albratty, Mohammed; Abadalla, Ashraf N; Lee, Learn-Han *; Goh, Khang Wen; Long, Chiau Ming *; Bouyahya, Abdelhakim * (Elsevier, 2023)
Cancer progression is strongly affected by epigenetic events in addition to genetic modifications. One of the key elements in the epigenetic control of gene expression is histone modification through acetylation, which is regulated by the synergy between histone acetyltransferases (HATs) and histone deacetylases (HDACs). HDACs are thought to offer considerable potential for the development of anticancer medications, particularly when used in conjunction with other anticancer medications and/or radiotherapy. Belinostat (Beleodaq, PXD101) is a pan-HDAC unsaturated hydroxamate inhibitor with a sulfonamide group that has been approved by the U.S. Food and Drug Administration (FDA) for the treatment of refractory or relapsed peripheral T-cell lymphoma (PTCL) and solid malignancies or and other hematological tissues. This drug modifies histones and epigenetic pathways. Because HDAC and HAT imbalance can lead to downregulation of regulatory genes, resulting in tumorigenesis. Inhibition of HDACs by belinostat indirectly promotes anti-cancer therapeutic effect by provoking acetylated histone accumulation, re-establishing normal gene expressions in cancer cells and stimulating other routes such as the immune response, p27 signaling cascades, caspase 3 activation, nuclear protein poly (ADP-ribose) polymerase-1 (PARP-1) degradation, cyclin A (G2/M phase), cyclin E1 (G1/S phase) and other events. In addition, belinostat has already been discovered to increase p21WAF1 in a number of cell lines (melanoma, prostate, breast, lung, colon, and ovary). This cyclin-dependent kinase inhibitor actually has a role in processes that cause cell cycle arrest and apoptosis. Belinostat's clinical effectiveness, comprising Phase I and II studies within the areas of solid and hematological cancers, has been evidenced through several investigative trials that have supported its potential to be a valuable anti-cancer drug. The purpose of this research was to provide insight on the specific molecular processes through which belinostat inhibits HDAC. The ability to investigate new therapeutic options employing targeted therapy and acquire a deeper understanding of cancer cell abnormalities may result from a better understanding of these particular routes.